Consolidation or maintenance systemic therapy for newly diagnosed stage II, III, or IV epithelial ovary, fallopian tube, or primary peritoneal carcinoma: A systematic review. (June 2021) - Hirte, Hal; Yao, Xiaomei; Ferguson, Sarah E.; May, Taymaa; Elit, Laurie
Highlights: Consolidation therapy with chemotherapy has no benefit in target EOC patients. Olaparib maintenance therapy had a higher PFS than placebo in patients with BRCA . Niraparib maintenance therapy led to a greater PFS than placebo in target patients. Veliparib maintenance therapy concurrent with adjuvant therapy has benefit in PFS. Bevacizumab maintenance from adjuvant therapy has benefit in high-risk patients. Abstract: Backgrounds: To systematically review the effectiveness and harm of consolidation or maintenance therapy in patients with newly diagnosed stage II-IV EOC. Methods: MEDLINE, EMBASE, PubMed, Cochrane Library, and PROSPERO databases, and four relevant conferences were systematically searched. We adhered to PRISMA guidelines, and used the GRADE approach to aggregate data. Results: Among 12, 675 citations, 28 comprising 16, 310 patients were analyzed. The certainty of aggregated study evidence ranged from high to low. Conclusions: The existing evidence does not find overall survival benefit for consolidation therapy with chemotherapy. For maintenance therapy, comparing with placebo, olaparib, niraparib, veliparib, and bevacizumab are effective as maintenance therapy for certain patients with newly diagnosed stage III-IV epithelial ovarian, fallopian tube, or primary peritoneal carcinoma respectively without reducing quality of life. Longer follow-up with more mature results of overall survival will better define the effect of these agents.